The impact of floods triggered by natural dam breakage on the adaptability of downstream river fish—the 2018 baige outburst flood in the upper reaches of the Yangtze river in China - Xie, Xinlin; Jiang, Xiangang; Wen, Tao; Jiang, Qing; An, Xinyu (Frontiers in Earth Science, 2024)
Outburst floods can affect the survival adaptability of fish. Although the survival adaptability of many fish species under low steady-flow conditions has been studied, research on the survival adaptability of fish species under large outburst flood conditions is lacking. This paper takes the 2018 Baige landslide dam as an example. A breach model was developed to calculate the outburst discharge of the landslide dam. The outburst flood hydrograph is simulated with the breach model, which shows that the difference between the peak discharge of the dam break simulation results and the measured data is 0.13×10 4 m 3 /s. In addition, the simulated hydrographs are the same as the measured hydrographs.Furthermore, a two-dimensional fish habitat model was used to analyse the adaptability of Schizothorax to survival during the breaching process. For the survival adaptability of Schizothorax, we observed that as the flow rate increased the weighted usable area (WUA) decreased, which indicated a decrease in the adaptability of Schizothorax survival. In contrast, as the flow rate decreased and the WUA increased, the survival adaptability of Schizothorax improved. In addition, the WUA of Schizothorax changed with the substrate of the riverbed; the smaller the channel suitability index (CSI) the greater the WUA.This study revealed the impact of outburst floods triggered by landslide dam failure on the survival adaptability of Schizothorax, and a method for assessing the impact of outburst floods on fish habitat adaptability is provided.